COMPUTER MODULE OF THE KDAM PROGRAM FOR DETERMINATION OF KINEMATIC AND DYNAMIC PARAMETERS OF THE PULLEY GROUP - SHCHERBAN, VOLODYMYR; KOLISKO, OKSANA; MELNIK, GENADIJ; KIRICHENKO, ANTON; SHCHERBAN, YURYJ (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The structural module of the KDAM computer program for determining the kinematic and dynamic parameters of the rocker group of mechanisms of textile and light industry machines allows you to determine coordinates, projections of velocities and accelerations of the center of mass of the rocker, rocker stone, and points of attachment of links of Asura groups to the rocker and rocker stone. During the dynamic analysis of the operation of the rocker group, the projections of the full reaction in the hinges between the crank and the rocker stone, between the rocker stone and the rocker, between the rocker and the fixed support are determined. In the case of connecting the rocker stone to a fixed support, the projections of the total reaction in the hinges between the crank and the rocker, between the rocker and the rocker stone, and between the rocker stone and the fixed support are determined. The obtained results are used in the program to assess the intensity of the technological processes of the textile industry when determining the change in the relative tension of the thread in the filling zones on the textile equipment. Kinematic and dynamic analysis of flat mechanisms of textile machines, which include ball groups, plays a significant role in the design of new mechanisms and modernization of existing ones. The results of these studies can be used to calculate the strength of individual links, their inertial characteristics, optimization of design parameters of textile machine mechanisms, and minimization of energy consumption. The use of a computer program allows you to determine tensions and changes in relative tension in the filling zones of textile industry machines, which allows you to optimize the shape of the thread feed line even at the stage of designing the technological process. The main parameter for the optimization of the thread supply system on the technological equipment of the textile and knitting industry is the minimum required tension in the working area. An increase in tension in the working area leads to thread breakage and, as a result, to the stoppage of the technological equipment. Downtime of the equipment related to the liquidation of the break currently accounts for 75-80% of the total downtime.Computer determination of kinematic and dynamic parameters of flat mechanisms, which include ball groups, allows to determine the parameters used in determining the intensity of technological processes of the textile industry.